How observations on wards led to a change in the Danish national guideline. Issue 2 (12th March 2012) - Herkell, K.; Colberg, L.; Schrøder, A.; Armandi, H.B.; Beck, P.
Abstract : Background: Patients poisoned with paracetamol are treated with the antidote N-acetylcysteine (NAC). According to the previous Danish national guidance the first infusion with NAC has to be mixed in 300 ml 5% glucose (or isotonic NaCl). In Denmark 300 ml solutions are only supplied in glass bottles. These are not designed to be used with IV poles. As an alternative 500 ml solution are supplied in infusion bags designed to be used with IV poles. This requires the nurse to withdraws 200 ml of the solution. Pharmacy staff from the Capital Region had been asking the Medicines Information Centre (MIC) whether it was possible to use 250 ml of glucose solution instead of 300 ml. Purpose: The task was to investigate the possibility of changing practice when preparing NAC infusions, in order to secure easier, faster and more rational treatment of patients poisoned with paracetamol. Materials and methods: Pharmacy staff visiting hospital wards daily had independently been observing the inappropriate and time-consuming preparation of NAC infusions. The MIC was asked to provide a more manageable handling routine in the hospital. The MIC task involved: ▶ Reviewing the antidote/emergency management guidelines ▶ Reviewing the relevant literature regarding treatment with NAC ▶ Discussing the case with the clinical pharmacologist connected to the national Danish Poison Control Hotline. Results: The conclusion finally resulted in a change in the national guideline for the treatment of paracetamol poisoning. This change of volume for preparation of NAC infusions further provided additional benefits: ▶ faster initiation of treatment ▶ improved patient safety due to simpler handling ▶ price reduction of approximately 10€ per treatment Conclusions: The MIC concluded that 250 ml solution can be used equivalent to 300 ml.